Ribemont-sur-Ancre, ritual practice, and northern Gallic sanctuaries from the third through first century B.C. - Rose, David Steven (The University of Edinburgh, 2020)
The following thesis addresses the Iron Age origins and development of the northern Gallic sanctuary of Ribemont-sur-Ancre, exploring the material remains of ritual practice it provides in comparison with material from neighbouring sanctuaries and sacred contexts. The material remains fall into three categories: human bones, animal bones, and iron armament, which will be examined individually in three main chapters. Chapter 1 introduces the questions to be addressed in the thesis and the material under discussion. Chapter 2 introduces the sanctuary of Ribemont andpresents an extended comparison with the sanctuary of Gournay-sur-Aronde and the cult enclosure within the aristocratic residence of Montmartin that will be the basis of the arguments made about Ribemontin Chapters 3–5. Chapter 2 examines the foundation, nature,and development of the installations that defined the sanctuary –the circular enclosure, quadrangular enclosure, and mass grave–and their chronology. It provides context forinterpretingthe material remains in the subsequent chapters. Chapter 3.Human Bones is primarily devoted to discussing the remains of more than five hundred warriors found at Ribemont. The human bones from Ribemont, like the armament, are divided between the three La Tène installations. This massive and unparalleled collection of corpses was subjected to complex, multi-stage ritual treatments, which differed by installation. Corpses were exposed to the elements, dismembered, de-fleshed, and some were built into cubic bone structures within the quadrangular enclosure. Employing comparative evidence from other northern Gallic sites, the chapter argues that human sacrifice, and the processing of corpses on these sites, was by no means straightforward, and did not correspond to classical authors’ portrayals of the Gauls. Chapter 4. Animal Bones explores banqueting practice within sacred contexts, large scale butchering with the distribution of meat and display of butchering remains, and non-consumption animal sacrifices, arguing that while ritual precepts were shared across multiple sites, each site had its own particular character.The significance of the ritual precepts and displays of remains are also addressed.Non-consumption animal sacrificesare discussed in comparison with the ritual treatments of human corpses, with which they share several commonalities. Chapter 5. Armament examines the assemblagesfrom the sanctuaries of Ribemont-sur-Ancre andGournay-sur-Aronde, the two largest collections in northern Gaul, in comparison with each other. The chapter addresses the problems with previous interpretations of the armament from Ribemont, which viewed it as a monolithic collection from a third century B.C. battle near the site. Like the human remains, the armament from Ribemont is divided across the three contexts ofthe site: the circular enclosure, quadrangular enclosure, and mass grave. While the assemblages from these contexts are largely similar, there are distinct differentiating elements in the nature and disposition of each assemblage. While the majority of the armament does seem to originate from a short conflict period, significant minorities of arms date to the decades before and the centuries after, comprising a collection dating from the third through the late first century B.C. The implications of this continuity will be discussed in comparison with the century-long dedicatory tradition at Gournay. In addition, the ritual mutilation of armament, a significant minority practice at Ribemont, finds parallels in the well-known ritual mutilation of armament at Gournay. The conclusion (chapter 6) provides a synthesis, addressing how the three categories of material remains illustrate the interwoven and multifaceted ritual practice at Ribemont-sur-Ancre and other sanctuary sites in northern Gaul. While Ribemont-sur-Ancre is well-known, its true history and nature in the Iron Age, and the material remains it provides, are poorly understood. This thesis will provide a revised interpretation of the La Tène history, structures, and material from Ribemont in order to address this deficiency. It is hoped that the ritual practices at Ribemont and other Iron Age sanctuaries will be better understood as a result.
Keywords: Iron Age; Ribemont-sur-Ancre; Gallo-Roman Temples; armament; human bones; animal bones; La Tene period; ritual; ritual practice; Northern Gaul; pre-Roman; material culture